Methods to estimate collision risk and behavioural responses of seabirds around wind turbines in the Firth of Forth ... - Repas-Goncalves, Miguel; Pina, Luis; Barton, Collin; Cardia, Pedro; Oliveira, Ricardo; Perrow, Martin; Segurado, Pedro; Tarrant, Polly; Machado, Rui; May, Roel (Zenodo, 2023)
The development of wind energy is crucial for mitigating the impacts of climate change. Offshore wind farms are an increasingly used source of renewable energy but there are concerns of their potential effects on wildlife, particularly on seabirds. To address this issue, a comprehensive study has been devised to monitor the impact of the Neart na Gaoithe offshore wind farm, off the east coast of Scotland on two seabird species: northern gannet and black-legged kittiwake. The study will be conducted over a two-year period and will provide a detailed understanding of how these species interact with wind turbines and how they adapt to the changing environment. It will focus on acquiring empirical measures of collision rates and collision risk (micro-avoidance), as well as obtaining three-dimensional records of flight behaviour around wind turbines and the area surrounding the windfarm, to characterize meso- and macro-avoidance responses. A setup comprising three dual radar sets (horizontal and vertical radars), ... : Conference presentations and posters are typically about preliminary findings and are usually followed up by a detailed paper. This poster is based only on its abstract and may offer limited information. Please contact us for the detailed project brief, which may offer additional information that you can utilize for your research. This study was commissioned to STRIX, financed by the Forth and Tay developers of Neart na Gaoithe Offshore Wind Ltd, Seagreen Wind Energy Limited and Berwick Bank Wind Farm. The study has been devised in collaboration with RSPB, NatureScot, Joint Nature Conservation Committee and Marine Scotland Science, and endorsed by the Forth and Tay Regional Advisory Group. A study of such scale and detail is a first in the UK. ...